1998
DOI: 10.3354/meps174067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dissolved oxygen on the energy balance and survival of Penaeus setiferus juveniles

Abstract: Penaeus setiferus, the white shrimp from the Gulf of Mexico, is an abundant species in the coastal lagoons and estuaries, where it can experience anoxic conditions. This study was designed with the purpose of measuring the effects of dissolved oxygen (DO] on the assimilation of ingested food (AS), by measuring the respiratory rate (R) and the biomass production of P. setiferus during its growth (P) process (AS = R + P). Postlarvae of this species (PLz7: 27 d after the last metamorphic molting) were exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 17 publications
3
24
0
1
Order By: Relevance
“…The large plankton production and vertical stratification driven by the MS-A river system discharge promote the development of a hypoxic bottom layer a few meters thick off Louisiana and Texas during summer (Obenour et al, 2013). This hypoxic layer can negatively impact metabolism and growth of fish and invertebrates (Rosas et al, 1998;Craig and Crowder, 2005), and disturb species distribution and composiPublished by Copernicus Publications on behalf of the European Geosciences Union. 3562 F. A.…”
Section: Introductionmentioning
confidence: 99%
“…The large plankton production and vertical stratification driven by the MS-A river system discharge promote the development of a hypoxic bottom layer a few meters thick off Louisiana and Texas during summer (Obenour et al, 2013). This hypoxic layer can negatively impact metabolism and growth of fish and invertebrates (Rosas et al, 1998;Craig and Crowder, 2005), and disturb species distribution and composiPublished by Copernicus Publications on behalf of the European Geosciences Union. 3562 F. A.…”
Section: Introductionmentioning
confidence: 99%
“…Third, biological mechanisms that link hypoxia to shrimp abundance produce sharp predictions about the shrimp market. Bioenergetic consequences of hypoxia likely translate into impaired growth (12)(13)(14)(15)(16), reducing the average size of shrimp in the population. Shrimp also aggregate along the edges of the hypoxic area such that segments of the population are exposed to increased catchability early in the season when shrimp are small (12)(13)(14).…”
mentioning
confidence: 99%
“…Moreover, shrimp invest more time in assimilation of food at these lower levels of dissolved oxygen (Rosas et al 1998). Another study identified a negative effect of severe hypoxia (1 mg/l dissolved oxygen) on the immune response of Penaeus stylirostris shrimp, further noting that the mortality of the hypoxia-stressed shrimp significantly increased when experimentally injected with a virulent (Moullac et al 1998).…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…For example, juvenile white shrimp can survive moderately low levels of dissolved oxygen, but their growth rates decrease when exposed to dissolved oxygen levels below 4 mg/1 (Rosas et al 1998).…”
Section: Empirical Backgroundmentioning
confidence: 99%